2022
DOI: 10.1186/s12886-022-02518-4
|View full text |Cite
|
Sign up to set email alerts
|

Chorioretinal thickness and retinal pigment epithelial degeneration of fellow eyes in patients with unilateral neovascular age-related macular degeneration with subretinal drusenoid deposits

Abstract: Background We sought to investigate the chorioretinal thickness and retinal pigment epithelial (RPE) degenerative features of eyes with early age-related macular degeneration (AMD) and subretinal drusenoid deposits (SDDs) according to the presence of macular neovascularization (MNV) in the fellow eyes. Methods We classified 70 eyes into two groups of 47 eyes with non-neovascular AMD and 23 eyes with neovascular AMD, respectively, according to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Kang et al investigated the chorioretinal thickness and RPE degenerative features of eyes with AMD and SDDs according to the presence of MNV in the fellow eyes [34]. Several studies suggested that early AMD eyes with SDDs are prone to overall chorioretinal degeneration, including of the RPE [58].…”
Section: Predicting the Type Of Mnv In The Fellow-eyementioning
confidence: 99%
“…Kang et al investigated the chorioretinal thickness and RPE degenerative features of eyes with AMD and SDDs according to the presence of MNV in the fellow eyes [34]. Several studies suggested that early AMD eyes with SDDs are prone to overall chorioretinal degeneration, including of the RPE [58].…”
Section: Predicting the Type Of Mnv In The Fellow-eyementioning
confidence: 99%